Influence of postharvest UV-C treatment on refrigerated storage of minimally processed broccoli (Brassica oleracea var.Italica) - Lemoine, María Laura (2007)
Minimally processed broccoli was treated with UV-C light (8 kJ m−2) and subsequently stored for 21 days at 4 ◦C. The UV-C treatment delayed yellowing and chlorophyll degradation during storage. Treated broccoli florets displayed lower electrolyte leakage and respiratory activity, indicating higher tissue integrity. Treated samplesshowed higher phenolic and ascorbic acid contents as well as higher antioxidant activity than controls. Treated samples also had a higher content of soluble sugars, but no differences in the content of soluble proteins between control and treated samples were detected. The UV-C treatment also affected bacterial and mould populations. After 21 days at 4 ◦C the number of colony-forming units of both populations was lower in treated than in control broccoli florets. The results suggest that UV-C treatment reduces tissue damage of minimally processed broccoli during storage at 4 ◦C, thus maintaining nutritional quality and reducing microbial growth.